Transients State Estimation with measurement noise - Naret Suyaroj (2018)
© 2015 IEEE. In order to determine the monitoring in large power system during disturbance, Transient State Estimation (TSE) algorithm combines partial measurement with state estimation technique to derive measurement value at unmonitored location in electric power system with transient phenomena. The measurement noises are taken into considering the efficiency of proposed algorithm. The test systems use 6 bus power systems with transient event that caused by a sudden lost of a load and apply the lost in different level which effect to dropping voltage from 10% till 90% at selected bus. The noise define to be normally distributed, is added to all of the measurements in 1%, 3% and 5% level. The results show that the Transient State Estimation (TSE) can remain good estimation with measurement noise at no measurement location.